Converting the Beef Cow Herd to a Controlled Breeding Season - Tim Wilson; Cindy Sanders; Mark Warren; Matt Hersom; Curt Lacy (EDIS)
Implementing a controlled breeding season to manage the length of the calving season is a cost-effective management practice. This 4-page fact sheet describes a 3- to 4-year conversion program beef cattle producers can follow. Written by Tim Wilson, Cindy Sanders, Mark Warren, Matt Hersom, and Curt Lacy, and published by the UF Department of Animal Science, August 2011.